At the Crossroad with Morbidity and Mortality Conferences: Lessons Learned through a Narrative Systematic Review - Xin Xiong; Teela Johnson; Dev Jayaraman; Emily G. McDonald; Myriam Martel; Alan N. Barkun (Canadian Journal of Gastroenterology and Hepatology)
Objective. To determine the process and structure of Morbidity and Mortality Conference (MMC) and to provide guidelines for conducting MMC. Methods. Using a narrative systematic review methodology, literature search was performed from January 1, 1950, to October 2, 2012. Original articles in adult population were included. MMC process and structure, as well as baseline study demographics, main results, and conclusions, were collected. Results. 38 articles were included. 10/38 (26%) pertained to medical subspecialties and 25/38 (66%) to surgical subspecialties. 15/38 (40%) were prospective, 14/38 (37%) retrospective, 7/38 (18%) interventional, and 2/38 (5%) cross-sectional. The goals were quality improvement and education. Of the 10 medical articles, MMC were conducted monthly 60% of the time. Cases discussed included complications (60%), deaths (30%), educational values (30%), and system issues (40%). Recommendations for improvements were made frequently (90%). Of the 25 articles in surgery, MMCs were weekly (60% of the time). Cases covered mainly complications (72%) and death (52%), with fewer cases dedicated to education (12%). System issues and recommendations were less commonly reported. Conclusion. Fundamental differences existed in medical versus surgical departments in conducting MMC, although the goals remained similar. We provide a schematic guideline for MMC through a summary of existing literature.